In-cylinder studies of hybrid combustion in a direct injection single-cylinder optical engine - Yang, C-H; Zhao, H (International journal of engine research, 2010)
Abstract Over the last decade, controlled autoignition (CAI) combustion, or homogeneous charge compression ignition (HCCI), has been the subject of numerous studies and has shown its potential to reduce fuel consumption and NO x emissions simultaneously from gasoline engines. However, there are still some fundamental questions that are yet to be addressed, such as combustion control and underlying physical and chemical processes. In the present study, a single-cylinder optical gasoline engine was operated with negative valve overlap to investigate CAI and hybrid spark ignition (SI)–CAI combustion. The effects of direct fuel injection and spark timings were studied by means of a simultaneous in-cylinder heat release study and high-speed visualization of total chemiluminescence, OH and CHO radicals.